Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 9 - Section 9.4 - Properties of Logarithms - Exercise Set - Page 713: 70



Work Step by Step

Note that $6=3(2)$. Thus, the given expression is equivalent to: $=\log_b{(3\cdot2)}$ RECALL: (1) $\log_b{(\frac{m}{n})} = \log_b{m} - \log_b{n}$ (2) $\log_b{mn} = \log_b{m} + \log_b{n}$ Use rule (2) above to obtain: $=\log_b{3} + \log_b{2}$ With $\log_b{2} = A$ and $\log_b{3}=C$, the expression above is equivalent to: $=C+A$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.